Fabrication of large-area microwells on Polydimethylsiloxane films by femtosecond laser ablation. (October 2020) - Ou, Yan; Li, Sheng; Qian, Jinwen; Xiao, Yifeng; Fu, Siyi; Wu, Liang; Zhang, Minghua
Highlights: All microwells were generated by temporally shaped femtosecond laser. Microwells profile can be controlled by adjusting the laser power and pulse delay. The smooth microwells have a high-quality optical properties. Abstract: In this paper, a novel technique was presented for fabricating microwell array in large areas on a Polydimethylsiloxane films using high-speed scanning of a laser beam. A femtosecond laser double pulse ablation was achieved on Polydimethylsiloxane films. Microwells with various dimensions and sub-microstructures were successfully fabricated on Polydimethylsiloxane films, which has many applications such as optical devices. In this paper, we demonstrate that the surface roughness of the microwells is related to the laser parameters and a smooth surface can be obtained. The smooth surface of the fabricated microwells could be applied in optical imaging systems as concave microlenses, in which enables the high-resolution imaging. We also demonstrated that the microwells were formed by the transient localized electron dynamics. This work could lead to a new approach to the fast fabrication of large-area microstructures using the ultrafast laser processing technologies.